Analisis Kinerja Keuangan Terhadap Return Saham Pada Perusahaan Konstruksi - Fry Melda Saragih; Petrus Sentoso Tan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Construction companies are one of the investment sectors in Indonesia in the country's economy. However, in recent years, construction sector stocks have experienced fluctuations, which has caused many construction sector issuers to sell their shares. This study aims to examine potential factors in influencing the influence of stock returns on the construction sector listed on the Indonesia Stock Exchange (IDX) in the 2016-2021 period. This research obtained data obtained from financial statements on companies listed on the IDX. Purposive sampling was used in this study in obtaining research samples. Nine companies were used in this study that met the criteria in purposive sampling. Based on the results of chow testing and hausman testing, and for the data analysis method, namely by using panel data regression with fixed-effect models, the results of this study show that the current ratio and total asset turnover have a significant effect on stock returns. However, the return on assets and debt to asset ratio have no effect on stock returns.